Development of Captopril Analysis Method in Traditional Antihypertensive Medicine by Densitometry - Risthanti, Reine; Sumartha, I Gede Ari; Alkindi, Fawandi Fuad; Budiono, Ryanto; Ananda, Rizka Widya (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Introduction: The utilisation of traditional medicine to address health concerns is on the rise. One such traditional medicine product is antihypertensive herbal medicine. The Indonesian Food and Drug Authority (BPOM) has identified the presence of medicinal chemicals in traditional medicinal products, which has the potential to pose a significant risk to consumers. Captopril is one of the antihypertensive drugs that may be added as BKO in herbal medicine. Aims: The objective of this study was to develop a method for the analysis of the chemical content of captopril in antihypertensive herbs sold online under the following brands: A, B, C, and D. Method: The analytical method used was TLC-densitometry, utilising a mobile phase of chloroform: methanol (7:3). Result: The results show that the method used has fulfilled the requisite validation criteria for linearity, limit of detection (LOD), limit of quantitation (LOQ), accuracy, and precision parameters. The results of the analysis demonstrated that the sample did not contain any detectable quantities of captopril. Conclusion: The developed method has been proven to be effective for the analysis of captopril in antihypertensive herbal products and it can be confirmed that there is no presence of captopril medicinal chemicals in samples from brands A, B, C, and D